Dawn of the light dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2023)
To prevent the Shadow Dragon from plunging the world into sky-shadow the Dragon Masters must seek out a Light Dragon. So Drake and Darma travel to find a Light Dragon named Lysa. Lysa's Dragon Master, Rune, who is deaf, explains that the Dragon Masters will need a Star Flute in order to summon a Star Dragon and stop the Shadow Dragon. But the flute is hidden within a dangerous labyrinth! Will they be able to make it out of the tricky maze?